2016
DOI: 10.1186/s13054-016-1500-5
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared spectroscopy for assessing tissue oxygenation and microvascular reactivity in critically ill patients: a prospective observational study

Abstract: BackgroundImpaired microcirculatory perfusion and tissue oxygenation during critical illness are associated with adverse outcome. The aim of this study was to detect alterations in tissue oxygenation or microvascular reactivity and their ability to predict outcome in critically ill patients using thenar near-infrared spectroscopy (NIRS) with a vascular occlusion test (VOT).MethodsProspective observational study in critically ill adults admitted to a 12-bed intensive care unit (ICU) of a University Hospital. NI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 34 publications
1
26
0
1
Order By: Relevance
“…Sublingual microcirculation has been evaluated extensively using handheld videomicroscopy [31], and alterations to the microvascular perfusion characteristics are seen following ICU interventions [32][33][34][35], and correlated with adverse ICU outcomes [36,37]. Dynamic assessments of peripheral perfusion using LDF [38,39] or StO2-derived vascular occlusion tests [40,41] also correlate with ICU outcomes, signifying the importance of the microcirculation in the pathophysiology of critical illness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sublingual microcirculation has been evaluated extensively using handheld videomicroscopy [31], and alterations to the microvascular perfusion characteristics are seen following ICU interventions [32][33][34][35], and correlated with adverse ICU outcomes [36,37]. Dynamic assessments of peripheral perfusion using LDF [38,39] or StO2-derived vascular occlusion tests [40,41] also correlate with ICU outcomes, signifying the importance of the microcirculation in the pathophysiology of critical illness.…”
Section: Discussionmentioning
confidence: 99%
“…Given the substantial between-patient heterogeneity observed in this cohort, larger sample sizes will be required with the addition of healthy volunteers as a comparison group; MHC signal complexity also suggests that the best metrics for characterizing microvascular dysfunction are not yet established. Furthermore, studies have shown that microvascular monitoring may not discriminate between survivors and non-survivors during initial evaluation, and that metrics will only separate later in ICU stay [41,66]. Thus, the prognostic ability of MHC monitoring is best evaluated with daily assessment to correlate MHC signal with ICU outcomes.…”
Section: Study Limitations and Future Considerationsmentioning
confidence: 99%
“…Dynamic VOT parameters had a higher accuracy in detecting microvascular dysfunction in critically ill patients than static values [30,36]. In a mix critically ill adults' population, Donati et al showed that the desaturation rate tended to be slower in the late ischemic phase in patients with sepsis, hypotension, high lactate levels or with norepinephrine administration (conditions of a likely hemodynamic instability) [37]. Although our study, involving a smaller population, evidenced similar descending slope rates between shock and non-shock patients, we observed lower values of StO 2 min in patients with shock compared with patients without shock, probably due to the imbalance between supply and demand of oxygen and lower auto regulatory reserve [38].…”
Section: Discussionmentioning
confidence: 99%
“…This may be particularly useful in conditions where a challenged microcirculation is part of the pathological mechanisms behind the tissue morbidity. Techniques for monitoring alterations in microcirculation of the skin have therefore, in recent years, been playing an increasingly important part in burn care (14); postoperative monitoring of free flaps (15) (16)(17)(18)(19); intensive care (20); and diagnosis of peripheral vascular (21) -and skin diseases (22). In some cases it is the viability of the skin itself that is of interest, whereas in other cases, the microcirculation of the skin can be used as a target for assessing the state of the underlying tissue, or even the whole body.…”
Section: Studying the Dermal Microcirculationmentioning
confidence: 99%